2015
DOI: 10.1002/2015wr017732
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of groundwater flow in mountainous, headwater catchments with permafrost

Abstract: Headwater catchments have a direct impact on the water resources of downstream lowland regions as they supply freshwater in the form of surface runoff and discharging groundwater. Often, these mountainous catchments contain expansive permafrost that may alter the natural topographically controlled groundwater flow system. As permafrost could degrade with climate change, it is imperative to understand the effect of permafrost on groundwater flow in headwater catchments. This study characterizes groundwater flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 49 publications
4
57
1
Order By: Relevance
“…Many groundwater modeling studies in permafrost regions have reported on the subsurface fluxes, including soil drainage and recharge, and suprapermafrost flow. These studies have also shown that SW-GW exchanges can increase as the 10 active layer thickening, with water uptake into suprapermafrost aquifer occurring when subpermafrost hydraulic heads rise (Bense et al, 2009(Bense et al, , 2012Evans et al, 2015;Ge et al, 2011). Although our observations did not demonstrate the impact of changes to the permafrost table, our results show increasing interactions between SW-GW with active layer thawing.…”
Section: Implications Of Sw-gw Interaction In Permafrost Regioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Many groundwater modeling studies in permafrost regions have reported on the subsurface fluxes, including soil drainage and recharge, and suprapermafrost flow. These studies have also shown that SW-GW exchanges can increase as the 10 active layer thickening, with water uptake into suprapermafrost aquifer occurring when subpermafrost hydraulic heads rise (Bense et al, 2009(Bense et al, , 2012Evans et al, 2015;Ge et al, 2011). Although our observations did not demonstrate the impact of changes to the permafrost table, our results show increasing interactions between SW-GW with active layer thawing.…”
Section: Implications Of Sw-gw Interaction In Permafrost Regioncontrasting
confidence: 55%
“…Groundwater contributes significantly to stream baseflow, with most groundwater flow presented as a suprapermafrost aquifer (Evans et al, 2015). Many groundwater modeling studies in permafrost regions have reported on the subsurface fluxes, including soil drainage and recharge, and suprapermafrost flow.…”
Section: Implications Of Sw-gw Interaction In Permafrost Regionmentioning
confidence: 99%
“…With the increasing demand on limited water supplies, particularly in arid and semiarid regions, the potential effects of climate change on water resources in mountainous regions have received considerable attention in recent years [Brooks et al, 2015;Evans et al, 2015;Viviroli et al, 2011;Zhang et al, 2016]. In many large watersheds, surface water and interbasin groundwater flows, which originate from mountainous areas, provide the major sources of water for densely populated downstream alluvial plains.…”
Section: Introductionmentioning
confidence: 99%
“…Wellman et al [18] demonstrated that permafrost thaw could accelerate rates of groundwater flow in the active layer above permafrost. Evans et al [19] suggested that an increase in mean annual surface temperature of 2 ‱ C could cause a three-fold increase in groundwater contribution to discharge.…”
Section: Introductionmentioning
confidence: 99%